Adherence to guideline recommendations for human rabies immune globulin patient selection, dosing, timing, and anatomical site of administration in rabies postexposure prophylaxis. Issue 1 (2nd January 2020) - Hwang, Grace S.; Rizk, Elsie; Bui, Lan N.; Iso, Tomona; Sartain, Emily I.; Tran, Anh Thu; Swan, Joshua T.
ABSTRACT: Rabies is a fatal disease that mandates proper prophylaxis after a rabies virus exposure to prevent death. This study evaluated adherence to Centers of Disease Control and Prevention (CDC) recommendations for rabies immune globulin (IG) patient selection, dosing, timing of administration, and anatomical site of administration for rabies postexposure prophylaxis. This retrospective, cross-sectional study included patients who received at least one dose of rabies IG or rabies vaccine at a multi-hospital health system from January 2015 through June 2018. This study included 246 patients, and all of them received at least one dose of rabies vaccine. Two patients had a history of rabies vaccination, did not have an indication for rabies IG, and appropriately did not receive additional rabies IG. Rabies IG was administered to 91% (223 of 244) of patients with an indication. Of 223 patients who received rabies IG, 219 (98%) received doses within 10% of 20 IU/kg of body weight, and all 223 (100%) received rabies IG within 7 days of the first rabies vaccine administration. Only 56% (96 of 170) of patients with a wound that could be infiltrated with rabies IG actually received rabies IG via infiltration into and around the wound. This multi-hospital health system study demonstrated high adherence to guideline recommendations for rabies IG patient selection (91%), dosing (98%), and timing (100%). However, only 56% of eligible patients received rabies IG infiltration at wound sites as recommended by guidelines.